2013
DOI: 10.5430/ijhe.v2n4p172
|View full text |Cite
|
Sign up to set email alerts
|

The Integrative Model of Behavior Prediction to Explain Technology Use in Post-graduate Teacher Education Programs in the Netherlands

Abstract: This study examined technology in post-graduate teacher training programs in the Netherlands. A questionnaire was completed by 111 teacher educators from 12 Dutch universities with a post-graduate teacher training program. The general view of the use of technology in Dutch post-graduate teacher education was quite conventional. Basic technology such as computers, WiFi, electronic whiteboards, virtual learning environments and presentation software was commonly used, but more advanced or innovative technology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
2
12
0
2
Order By: Relevance
“…These results fitted in with other studies using raa and its predecessors. Attitude having the strongest influence on intention was seen many times before and a significant influence from only two out of the three proximal variables was also seen in previous studies (Admiraal et al, 2013;Kreijns et al, 2013;Lee et al, 2010;Sugar, Crawley, & Fine, 2004;Teo & Lee, 2010). Interestingly in this study, when the first hypothesis was tested again on the subgroup of smartphone owners, perceived norm no longer had a significant influence but perceived behavioural control did.…”
Section: Discussionsupporting
confidence: 71%
“…These results fitted in with other studies using raa and its predecessors. Attitude having the strongest influence on intention was seen many times before and a significant influence from only two out of the three proximal variables was also seen in previous studies (Admiraal et al, 2013;Kreijns et al, 2013;Lee et al, 2010;Sugar, Crawley, & Fine, 2004;Teo & Lee, 2010). Interestingly in this study, when the first hypothesis was tested again on the subgroup of smartphone owners, perceived norm no longer had a significant influence but perceived behavioural control did.…”
Section: Discussionsupporting
confidence: 71%
“…In the Netherlands, teaching in school is already a significant part of the teacher preparation programmes. This might support more student teachers' understanding of the substantive relationship between technology, pedagogy, learning, learners and learning outcomes, although recent research into the Dutch context does not suggest this; Dutch student teachers and teachers in primary and secondary education were generally not satisfied with how they were prepared for teaching with technology (Admiraal, Lockhorst, Smit, & Weijers, 2013;Hovius & van Kessel, 2013).…”
Section: Technology Approaches In Teacher Educationmentioning
confidence: 99%
“…The results from a study on ICT in Dutch teacher education programmes (Admiraal et al, 2013) suggest that both school teachers and teacher educators generally need to improve their own knowledge of and skills in technologyintegrated subject teaching. This implication for the professional development of educators is consistent with conclusions from Wetzel et al (2014), who found that teacher candidates advised teacher educators to feature more hand-on opportunities, modelling, and technological and pedagogical content knowledge.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Because intention to use technology was perceived as a behaviour that could be influenced by beliefs and skills (such as self-efficacy and technology integration) this subscale was ideal. Moreover, this model has been used recently to explain preservice teachers' intentions to use technology (Admiraal, Lockhorst, Smit, & Weijers, 2013Kreijns,Vermeulen, Kirschner, Van Buuren, & Van Acker, 2013. Computing the mean score for all three items created a singular intention variable.…”
Section: Part 2 -Intention To Integrate Technologymentioning
confidence: 99%